The Analyses of Role of Nursing Agency of Nurse and Family in Germas Behavior to Increasing the Preventive of Stroke to High Risk Patient Around the Public Health Center of Poncokusumo Subdistrict Malang Regency - Wijayanto, Herman Adhi (Master of Public Health Program Universitas STRADA Indonesia, 2020)
In high risk groups have a higher risk of stroke, so the role of family and nurse nursing agencies is needed in prevention efforts. The thing that is needed is to nurse and family to effort for improve healthy behavior. The purpose of this study was to determine the effect of nurse and family nursing agency roles on GERMAS behavior. The research design used was cross sectional with questionnaire sheet instruments. The population of this study was a high risk group of strokes in as many as 256. Samples were 155 using random sampling techniques, while to determine the effect between variables used ordinal regression test with a significant level of 0.05. Based on the results of the study, it was found that the role of nursing nurses was good 72 (46.5%) and most of the family nursing agency roles were quite good, 85 (54.8%) and good ,16 (10,3%) and GERMAS behavior good categories, 108 (69.7%) respondent. The results of data analysis show that the value of P value = 0,000. The results of statistical tests show that there is a significant influence between the role of nurse and family nursing agency on behavior. The existence of a good role from family and nurses with the existence of supervision and information from nurse and family will be able to change individual behavior for the better because the success of prevention depends on the readiness of the nursing agency to carry out their duties in the field of care properly and correctly